Meningkatkan Aktivitas Dan Motivasi Belajar Siswa Menggunakan Model Planet Pada Muatan IPA Kelas VB Di SDN 1 Lanjas - Akbara, Noval Satria; Suriansyah, Ahmad (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The problem in this study is the low activity, motivation, and learning outcomes. This is caused by the lack of student participation in learning, lack of use of teaching media, monotonous learning, and lack of encouragement and enthusiasm for students to carry out learning. Efforts to overcome these problems are by using the PLANET model. The purpose of this study is to describe teacher activities, describe student activities, describe student learning motivation, and analyze student learning outcomes. The subjects of the study were 26 students of class VB at SDN 1 Lanjas. Teacher activities, student activities, and student learning motivation were presented in qualitative data, while student learning outcomes were presented in quantitative data obtained through written tests. This study used descriptive analysis and cross-tabulation techniques, which were explained in the form of graphs, tables, and percentage interpretations. The results showed that teacher activity improved in each meeting reaching the "very good" criteria, student activity increased to "almost all students are active," and student learning motivation increased to "almost all students are highly motivated." Cognitive, affective, and psychomotor learning outcomes of students improved in each meeting and achieved the predetermined success indicators. Based on the findings, it can be concluded that there was an increase in teacher activity, student activity, student learning motivation, and student learning outcomes using the PLANET model.